2017
DOI: 10.1111/apa.14083
|View full text |Cite
|
Sign up to set email alerts
|

National allergy programme had little impact on parent‐reported food allergies in children aged 6–7 years

Abstract: We studied the national allergy programme that started in 2008 and found that there was a nonsignificant overall decrease in the number of children aged six to seven years on avoidance diets for allergies between 2009 and 2016. The only allergies that showed significant decreases were fresh fruit and vegetables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
(35 reference statements)
1
4
0
Order By: Relevance
“…and many of the unnecessary diets suspended in Step 2 of the study were attributed to avoidance of milk or egg. Our results show that these diets easily remain unmonitored even after tolerance to foods is achieved, as also demonstrated in a recent surveillance work 18. The reasons behind this phenomenon are most likelyhabitual and slow clinical follow-up.…”
supporting
confidence: 78%
“…and many of the unnecessary diets suspended in Step 2 of the study were attributed to avoidance of milk or egg. Our results show that these diets easily remain unmonitored even after tolerance to foods is achieved, as also demonstrated in a recent surveillance work 18. The reasons behind this phenomenon are most likelyhabitual and slow clinical follow-up.…”
supporting
confidence: 78%
“… The prevalence of self-reported wheat allergy; ( A ): the subgroup analysis for age; ( B ): the subgroup analysis for economy; ( C ): the subgroup analysis for region, ( D ): the subgroup analysis for timespan [ 18 , 19 , 21 , 23 , 26 , 27 , 28 , 30 , 31 , 32 , 34 , 35 , 36 , 37 , 41 , 42 , 44 , 46 , 47 , 49 , 50 , 51 , 54 , 55 , 56 , 57 , 59 , 62 , 63 , 66 , 67 , 68 , 70 , 71 , 72 ]. …”
Section: Figurementioning
confidence: 99%
“…Approximately half (48%) of children at risk for anaphylaxis may not possess/carry a designated AAI device [ 71 ], highlighting a need for stock AAI at schools. A 2019 cost-effectiveness study compared two school epinephrine supply strategies and demonstrated that stocking two unprescribed twin-pack units in addition to student’s individual AAI is cost-effective when total school adrenaline acquisition expenses do not exceed €311/school/year [ 72 ].…”
Section: Unique Considerations At Schoolsmentioning
confidence: 99%